Effectiveness of cyriax friction massage along with ultrasound therapy in patients with Plantar fascitis. - ANNA JACQUELINE ABIGAIL; KAMALAKANNAN.M (International Journal of Pharma and Bio Sciences, 2017)
Plantar fasciitis, a repetitive strain injury of the medial arch and heel, is one of the most common causes of foot pain.1 Aim is to determine the effectiveness of cyriax transverse friction massage with ultrasound therapy in the management of plantar fasciitis. Objective is To determine the effectiveness of ultrasound therapy with cyriax transverse friction massage on pain and functional ability in patients with plantar fascitis. Methodology: 30 Individuals were selected according to the inclusion and exclusion criteria. Participants were randomly assigned into two groups group A and group B. Pain was measured with Numerical Pain Rating Scale (NPRS), Foot function index (FFI) used to measure quality of life. Results: The post-test mean value of NPRS in Group-A is 3.47(SD 0.74) and post-test mean value of NPRS in Group-B is 1.40 (SD 0.63), this shows that Group-A is greater than Group-B with the P value (0.001),The post-test mean value of FFI in Group-A is 93.00 (SD 1.65) and post-test mean value of FFI in Group-B is 88.3 (SD 1.29), this shows that Group-A is greater than Group-B with the P value (0.001). It has been concluded that Cyriax tranverse friction massage with ultrasound therapy (Group B) is more effective than (Group A) in decreasing painand improving the functional ability.